2020
DOI: 10.1002/cncr.32703
|View full text |Cite
|
Sign up to set email alerts
|

Burden of comorbidities is higher among elderly survivors of oropharyngeal cancer compared with controls

Abstract: Background The prevalence of survivors of oropharyngeal cancer (OPC) is increasing due to improved survival for individuals with human papillomavirus (HPV)–related disease. Although elderly survivors of OPC are known to have a high burden of comorbidities, to the authors' knowledge it is unknown how this compares with a similar cohort without a history of cancer. Methods The current retrospective, cross‐sectional study included individuals with a first incident primary diagnosis of OPC from 2004 through 2011 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Due to the low number of studies that reported the incidence of ischemic stroke and ICH at 1, 3, and 6 months, we only evaluated the cumulative incidence of total stroke (i.e., sum of events) at these timepoints. Five studies reported the incidence of stroke at 1 month ( 12 , 16 , 35 37 ), four reported the incidence of stroke at 3 months ( 12 , 31 , 35 , 36 ), and eight reported the incidence of stroke at 6 months ( 12 , 14 , 16 , 17 , 31 , 35 , 36 , 38 ). Their respective pooled incidences at 1, 3, and 6 months are 1.6% (95% CI 0.2–10.8%; I 2 = 99.78%), 1.0% (95% CI 0.3–2.8%; I 2 = 99.95%), and 1.3% (95% CI 0.6–2.9%; I 2 = 99.96%) ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the low number of studies that reported the incidence of ischemic stroke and ICH at 1, 3, and 6 months, we only evaluated the cumulative incidence of total stroke (i.e., sum of events) at these timepoints. Five studies reported the incidence of stroke at 1 month ( 12 , 16 , 35 37 ), four reported the incidence of stroke at 3 months ( 12 , 31 , 35 , 36 ), and eight reported the incidence of stroke at 6 months ( 12 , 14 , 16 , 17 , 31 , 35 , 36 , 38 ). Their respective pooled incidences at 1, 3, and 6 months are 1.6% (95% CI 0.2–10.8%; I 2 = 99.78%), 1.0% (95% CI 0.3–2.8%; I 2 = 99.95%), and 1.3% (95% CI 0.6–2.9%; I 2 = 99.96%) ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Out of 22 studies that reported the combined incidence of ischemic and hemorrhagic stroke at 1 year, eight were cohort studies that included multiple types of cancer ( Supplementary Figure 3 ) ( 12 , 14 , 15 , 25 , 27 , 31 , 33 , 34 ). The remaining 14 studies were limited to specific cancer subtypes including head and neck cancer ( n = 3) ( 16 , 24 , 28 ), hematologic malignancies ( n = 2) ( 19 , 29 ), breast cancer ( n = 2) ( 21 , 23 ), and thyroid cancer ( n = 2) ( 26 , 32 ). There was only one study for each of the following subtypes of cancer: pancreatic, cervical, prostate, colorectal, and hepatic ( 17 , 18 , 20 , 22 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We would like to thank Dr. Braillon for his response to our article. 1 He has thoughtfully highlighted several important issues.…”
Section: Reply To Survivors Of Cancer Despite Poor Quality Of Care Are Heroesmentioning
confidence: 99%